Design and Synthesis of Novel Indole Ethylamine Derivatives as a Lipid Metabolism Regulator Targeting PPARα/CPT1 in AML12 Cells - Yu-Chen Liu; Gang Wei; Zhi-Qiang Liao; Fang-Xin Wang; Chunxiao Zong; Jiannan Qiu; Yifei Le; Zhi-Ling Yu; Seo Young Yang; Heng-Shan Wang; Xiao-Bing Dou; Cai-Yi Wang (Molecules, 2023)
Peroxisome proliferator-activated receptor alpha (PPARα) and carnitine palmitoyltransferase 1 (CPT1) are important targets of lipid metabolism regulation for nonalcoholic fatty liver disease (NAFLD) therapy. In the present study, a set of novel indole ethylamine derivatives (4, 5, 8, 9) were designed and synthesized. The target product (compound 9) can effectively activate PPARα and CPT1a. Consistently, in vitro assays demonstrated its impact on the lipid accumulation of oleic acid (OA)-induced AML12 cells. Compared with AML12 cells treated only with OA, supplementation with 5, 10, and 20 μM of compound 9 reduced the levels of intracellular triglyceride (by 28.07%, 37.55%, and 51.33%) with greater inhibitory activity relative to the commercial PPARα agonist fenofibrate. Moreover, the compound 9 supplementations upregulated the expression of hormone-sensitive triglyceride lipase (HSL) and adipose triglyceride lipase (ATGL) and upregulated the phosphorylation of acetyl-CoA carboxylase (ACC) related to fatty acid oxidation and lipogenesis. This dual-target compound with lipid metabolism regulatory efficacy may represent a promising type of drug lead for NAFLD therapy.